Weight Gain During Pregnancy Based on Pre-Pregnancy Body Mass Index with Duration of Labor - Siska Nawang Ayunda Maqfiro; Triany Laila Pelu (EMBRIO: Jurnal Kebidanan, 2024)
Chronic Energy Deficiency and being overweight in pregnancy is a severe problem because it could cause many risks in labor. This study aimed to determine the association between weight gain during pregnancy based on Body Mass Index before pregnancy with the duration of labor. The type of research was analytical observational with a cross-sectional approach. Thirty respondents used the quota sampling technique. The Spearman-rank test showed a significant value of 0,039, so there was a significant relationship between weight gain during pregnancy and the duration of the first stage of labor in the latent phase. The significant value was 0,016, indicating a relationship between weight gain during pregnancy and the duration of the first stage of labor in the active phase. However, a significant value of more than 0,05 in the variable duration of the second, third, and fourth stages of labor. So, it was necessary to monitor weight gain and provide counseling on the impact of excessive weight gain during labor. In addition, women with excessive weight gain should be given more time during the first stage because the duration in the second until the fourth stage of labor would generally run so that it could reduce unnecessary interventions.